Expenditure interactions between municipalities and the role of agglomeration forces: A spatial analysis for North Rhine-Westphalia - Sebastian Langer (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2018)
This paper analyzes municipal expenditures in the light of horizontal fiscal interactions. I investigate total expenditures and a set of non-earmarked expenditure subcategories in the largest German federal state, North Rhine-Westphalia (NRW). The empirical analysis is based on a Spatial Durbin Model in a panel for the years 2009-2015. Using a two-regime spatial matrix, I also examine the impact of agglomeration on the intensity of public expenditure interactions, thus testing the hypothesis that an agglomerated region can decrease the amount of public goods without losing mobile factors to the periphery. The findings indicate that significant municipal expenditure interaction effects do exist. The reaction functions also vary for different expenditure subcategories. Unlike spillover effects and fiscal competition, yardstick competition is an insignificant source of potential interactions. Expenditure interaction is fiercer if there is less agglomeration in a municipality. Urbanized and populous municipalities appear to benefit from agglomeration economies, a fact that enables them to spend less. Robustness checks confirm the findings.
urn:nbn:de:bsz:14-qucosa-236245
Keywords: C31; F12; F15; J31; 330; Local Government Expenditure; Spatial Regression Analysis; Expenditure Interaction